2020
DOI: 10.1016/j.ijid.2020.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Influenza-attributable years of life lost in older adults in a subtropical city in China, 2012–2017: A modeling study based on a competing risks approach

Abstract: The aim of this study was to estimate influenza-attributable years of life lost (YLL) in older adults in subtropical Hefei, China during the years 2012-2017, based on a competing risks approach. Methods: The quasi-Poisson model was fitted to weekly numbers of all-cause deaths by 5-year age groups for older adults !60 years of age. The product of the weekly influenza-like illness consultation rate and the proportion of specimens that tested positive for influenza was taken as the measurement of influenza activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Based on our model, in older adults, influenza-associated excess mortality rates for CVD, IHD and stroke increased with age. Consistent with reports from the USA 18 and Hefei, 23 a subtropical city in China, the highest excess mortality rate was in the ≥85 years group. A study from Singapore found that the burden of influenza on CVD increased with age and was significantly associated with excess hospitalisations for CVD, mainly in people≥80 years old.…”
Section: Discussionsupporting
confidence: 86%
“…Based on our model, in older adults, influenza-associated excess mortality rates for CVD, IHD and stroke increased with age. Consistent with reports from the USA 18 and Hefei, 23 a subtropical city in China, the highest excess mortality rate was in the ≥85 years group. A study from Singapore found that the burden of influenza on CVD increased with age and was significantly associated with excess hospitalisations for CVD, mainly in people≥80 years old.…”
Section: Discussionsupporting
confidence: 86%
“…A recent example of using ( 10 ) is Hao et al. ( 2020 ) who considered influenza‐attributable life years lost before the age of 90.…”
Section: Outcomes Their Analysis and Interpretationmentioning
confidence: 99%
“…This is also related to the ventilator free days discussed in Section 2. A recent example of using ( 10) is Hao et al (2020) who considered influenza-attributable life years lost before the age of 90. Alternatively, one may consider the median time to improvement,…”
Section: "Average" Improvement or Recovery Timesmentioning
confidence: 99%
“…This is also related to the ventilator free days discussed in Section 2. A recent example of using ( 8) is Hao et al (2020) who considered influenza-attributable life years lost before the age of 90. Alternatively, one may consider the median time to improvement,…”
Section: Competing Events: Time To and Type Of First Eventmentioning
confidence: 99%